Colon hypersensitivity to distension, rather than excessive gas production, produces carbohydrate-related symptoms in individuals with irritable bowel syndrome - Major, Giles; Pritchard, Susan Elizabeth; Murray, Kathryn; Alappadan, Jan Paul; Hoad, Caroline; Marciani, Luca; Gowland, Penny A.; Spiller, Robin C. (Elsevier, 2017)
Background & Aims: Poorly digested, fermentable carbohydrates may induce symptoms of irritable bowel syndrome (IBS), via unclear mechanisms. We performed a randomized trial with magnetic resonance imaging (MRI) analysis to investigate correlations between symptoms and changes in small and large bowel contents following oral challenge.